Irrational thoughts towards driving vehicles of the post Basic Students in the Governorate of Interior in the Sultanate of Oman - Al-Rawahi, Juma Mohammed Hamad (Journal of Educational and Psychological Sciences, 2019)
The aim of the study was to investigate irrational ideas towards driving vehicles among post-primary education students in Al-Dakhlia Governorate in Oman. The study sample consisted of (151) students of post-primary education students who held driving licenses, selected by the available sampling method. The researcher used the irrational scale of ideas to lead the vehicles that he built to collect the study data, which consisted of (42) paragraphs. The results of the study showed that the irrational ideas for driving the vehicles spread in the population of the study at a medium level, with an average of (2.70). The majority of the paragraphs obtained a medium degree on the scale of irrational ideas towards driving the vehicles. Whereas two ideas attained high degrees: one of them was item (28) that indicated accidents happened due to rules violation and the item (36) which represented driving license. It was considered as the basic stone for driving a vehicle. In addition, nine items in the questionnaire obtained low degrees. They were items (24,23,21,20,19,18,12,10 &5). The results of the study showed that there were no statistically significant differences in irrational thoughts towards driving, due to the variable of accident exposure during driving. , And the existence of statistically significant differences due to the variable age for the benefit of those aged between 18 and 17, and the existence of differences of statistical significance due to the variable income of the guardian and was in favor of the level of income between (800-1199).
Keywords: irrational thoughts; driving vehicles; University of Nizwa